Skrining Fitokimia dan Antimikroba Ekstrak Daun Kirinyuh terhadap Bakteri Staphylococcus Aureus Dan Escherichia Coli - Nuriana Munte; Sartini sartini; Rosliana Lubis (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2017)
This reseach aims to determine the composition of secondary metabolites of kirinyuh leaf extract (Euphatorium ordoratum.L) and antimicrobial properties of the extract against Staphylococcus aureus and Escherichia coli. The study was conducted in three phases: the first phase is manufacture kirinyuh leaf extract (Euphatprium odoratum L) through maceration method using N-Hexane solvent and methanol. In stage II, phytochemical screening, namely the identification of secondary metabolites (alkaloids, flavonoids, terpenoids and steroids) to the crude extract of  leaves kirinyuh (Ephatorium odoratum L) in the form of antimicrobial properties of extracts against Staphylococcus aureus and with variations extract concentrations of 0%, 1 %, 5%, 10%, 15%, 20%, and 25% Echerichia coli and incubated at 37°C for 24 hours. The research found that such compounds secondary metbolit alkaloids, flavonoids, steronoid, and saponin, which dominates the secondary metabolites of four that alkaloid. While the screening test of phytochemical N-hexane extracts is not contain metbolit secondary compounds, testing against bacteria possess bioktivitas inhibition at concentrations of 15% with inhibition zone of 1.3 cm on Escherichia coli bacteria and 1.0 cm in bacteria Staphylococcus aureas. This shows kirinyuh leaf extracts have the ability as an anti-microbial.